2016
DOI: 10.2139/ssrn.2762275
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: The Difference between U.S. And European Loan Rates

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…Using the January 2004-December 2012 period, 8,867 syndicated loan announcements are obtained and used to examine the impact of the financial crisis. Similar to Gasbarro et al (2004), 16 we partition loans based on loan types: 13 The claim that more screening and monitoring are required for borrowers in the middle of the credit ratings is consistent with Diamond (1991) and Berg et al (2017). 14 Berg et al (2017) consider loan types, loan purpose, and borrower ratings in their analyses, and the partitions in this study parallels their approach.…”
Section: Methodsmentioning
confidence: 95%
“…Using the January 2004-December 2012 period, 8,867 syndicated loan announcements are obtained and used to examine the impact of the financial crisis. Similar to Gasbarro et al (2004), 16 we partition loans based on loan types: 13 The claim that more screening and monitoring are required for borrowers in the middle of the credit ratings is consistent with Diamond (1991) and Berg et al (2017). 14 Berg et al (2017) consider loan types, loan purpose, and borrower ratings in their analyses, and the partitions in this study parallels their approach.…”
Section: Methodsmentioning
confidence: 95%
“…In order to more thoroughly investigate loan announcements, we partition on loan type and loan purpose, similar to Berg et al (2016Berg et al ( , 2017 and Buca and Vermeulen (2017). We also use investment ratings as a proxy for information asymmetry.…”
Section: Related Literaturementioning
confidence: 99%
“…Investment ratings have a long history in the assessment of information asymmetry and corporate risk. Studies by Odders-White and Ready (2006), Yi and Mullineaux (2006), Wittenberg-Moerman (2008), and Berg et al (2016Berg et al ( , 2017 explore different aspects of investment ratings. Overall, they suggest that it is prudent for both bank and borrower to work collaboratively to reduce information asymmetry and to facilitate loan approval.…”
Section: Related Literaturementioning
confidence: 99%
“…That explanation solved the puzzle, but only for listed borrowers. Berg et al (2016) underscored that loan category matters, and showed that the puzzle vanishes for syndicated credit lines, which account for 70% of their full sample.Stressing that ratings are based on accounting ratios (Campbell and Taksler, 2003), which depend on standards that vary across jurisdictions, this paper shows that using region-specific ratings solves the SL puzzle, not only over the period covered by C&N, but also for a larger sample of SLs. …”
mentioning
confidence: 99%
“…That explanation solved the puzzle, but only for listed borrowers. Berg et al (2016) underscored that loan category matters, and showed that the puzzle vanishes for syndicated credit lines, which account for 70% of their full sample.…”
mentioning
confidence: 99%